Assessing Urban Land Surface Temperature Fluctuations Amidst the Covid-19 Pandemic: A Landsat 8 and Landsat 9 Study of Bandar Lampung City - Simarmata, Nirmawana; Santo, A Ki Asmoro (Tunas Geografi, 2023)
Community activities before, during, and after the Covid-19 pandemic have undergone significant changes. This is due to the limitation and exemption of activities set by the government which can also result in changes in surface temperature. Physical separation from the Large-Scale Social Restrictions (PSBB) has led to a decrease in communal activities like traffic and the industrial sector, which has a policy of allowing most employees to work from home. This study intends to examine variations in Bandar Lampung surface temperature that took place in 2020, 2021, and. Identifying surface temperature using remote sensing technology, including Landsat 8 and Landsat 9 images. Both of these images have advantages with a large number of bands, especially the presence of a Thermal Infrared Sensor (TIRS) wavelength which has a sensitivity to detect temperature. Utilization of this wavelength can distinguish parts of the earth's surface that have a hotter temperature than the surrounding area. The land surface temperature (LST) approach can be used to determine the dynamics of surface temperature variations before, during, and after the Covid-19 epidemic. Image processing and analysis are done using Google Earth Engine. The results of the analysis of surface temperatures before Covid, the image recording time in 2020 has a value range of 13oC - 32oC, during the occurrence of Covid, the 2021 recording time has a value range of 3oC - 33oC, while after Covid, the 2022 recording time has a value range of 18oC - 32oC.Keywords: Covid-19, Landsat 8, Landsat 9, LST